Hubungan Dukungan Suami Dengan Pelaksanaan Inisiasi Menyusu Dini (IMD) Di Wilayah Kerja Puskesmas Seulimeum Kabupaten Aceh Besar - Martina; Yuli Zuhkrina; Yuni Rahmayanti (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
IMD (Early Initiation of Breastfeeding) is a very important opportunity and must be given immediately to newborns by placing the baby on the mother's stomach. Breastfeeding starting with IMD makes a big contribution to reducing infant mortality. IMD can prevent 22% of infant deaths at the age of 28 months. This research aims to determine husband's support in implementing early breastfeeding initiation (IMD) in the Seulimeum ​​Community Health Center Working Area, Aceh Besar Regency. This research is an analytical research with a cross sectional approach. Sample determination was carried out using Non-Random Sampling using the Accidental Sampling technique, namely all mothers giving birth in the Seulimeum ​​Aceh Besar Community Health Center area from 20 June to 30 July 2024 with a total of 30 samples. The results of the research show that there is a significant relationship between husband's support and the implementation of early breastfeeding initiation (IMD) in the Seulimeum ​​Community Health Center Work Area, Aceh Besar Regency. The conclusion is that there is a significant relationship between husband's support and the implementation of early breastfeeding initiation (IMD) in the Seulimeum ​​Community Health Center Working Area, Aceh Besar Regency.